Defluorinative Cyclization of Enamides with Fluoroalkyl Halides Through Two Vicinal C(sp3)─F Bonds Functionalization - Yu‐Lan Chen; Wei Han; Yuan‐Yuan Ren; Mengtao Ma; Danhua Ge; Zhi‐Liang Shen; Kai Guo; Xue‐Qiang Chu (Advanced Science)
Abstract Introducing distinctive functional groups to expand the structural diversity and improve the intrinsic properties of parent molecules has been an essential pursuit in organic chemistry. By using perfluoroalkyl halide (PFAH) as a nontraditional, readily available, ideal 1,2‐difluoroalkenyl coupling partner, a defluorinative cyclization reaction of enamides for the construction of fluoroalkenyl oxazoles is first developed. The selective and controllable two‐fold cleavage of vicinal C(sp3)─F bonds in PFAH not only enables the introduction of a specific 1,2‐difluoroalkenyl moiety with ease but also results in the functionalization of two C(sp2)─H bonds of enamides without the need for metal catalyst, photocatalyst, oxidant, or light. The method can be applied to the late‐stage modification of complex molecules, synthesis of biological‐relevant oxazole analoges, and scale‐up synthesis, which all further highlight the real‐world utility of this protocol. Mechanistic studies reveal that the reaction possibly proceeds through a radical perfluoroalkylation, consecutive C─F bond heterolytic cleavage, and cyclization process. In addition, the in situ formed perfluoroalkyl radical which may also serve as an essential hydrogen abstractor.